Learning Local Cultural Values through the Tauco Monument: A Semiotic Study in the Context of Cianjur Society - Neng Wina Resky Agustina; Meiga Fristya Laras Sakti (Jurnal Pembelajaran Bahasa dan Sastra, 2025)
Traditional food can be used as a culinary tour that can elevate the image of a region. One of Indonesia's regions with a variety of conventional foods is Cianjur Regency. In Cianjur Regency, there is a tauco monument as a marker. This study explores the meaning of the signs on the Tuco monument. Charles Sanders Pierce's Semiotic Theory is used to analyze and interpret the signs on the monument. This article examines the meaning of the Tauco Monument through the lens of Charles Sanders Peirce's semiotics. It connects it with project-based learning that involves direct observation, discussion, and creation of works, encouraging students to understand and express symbolic meanings through narrative, descriptive, and expository texts, as well as relevant educational media to shape the character and language skills of the younger generation. The monument was created to present the characteristics of Cianjur Regency, especially in the culinary field, taco, which is the identity of Cianjur that is already known in Indonesia. To be used as a self-identity of the Cianjur community, the monument is rich in various superior regional potentials manifested in the form of a memorial. All of them are a self-identity or identity of the community that has been forgotten in achieving and realizing and being grateful for the provision of sufficient natural resource potential from Allah SWT to the Cianjur community; of course, it must be managed optimally to fulfil the rights of the Cianjur community fully.